ORAL HYGIENE IN 3-RD COURSE SAMARKAND STATE MEDICAL INSTITUTE DEPARTMENT OF PEDIATRIC DENTISTRY - Burxonov Jahongir; Shukurova N.T. (Journal of new century innovations, 2024)
Annotation. Students represent a special social group, characterized by specific living conditions, forced disruption of work, rest and nutrition, and severe psycho-emotional and mental stress [1]. Dental morbidity currently remains high in the student age group and does not tend to stabilize [2]. The weakest link in the implementation of measures for the primary prevention of major dental diseases is the hygienic education of the population and sanitary educational work [3]. Basic dental diseases: dental caries and periodontal diseases remain, as before, the most common diseases of the population throughout the world, as well as in our country. A significant portion of young people neglect the prevention of dental diseases and have low motivation to maintain dental health [1, 4, 5, 6]. The choice of specific means and methods of individual oral hygiene for each patient is the responsibility of the dentist. Also, doctors of all specialties should play an active role on issues of health education and oral hygiene in hygienic motivation, training the population and maintaining their constant preventive activity. Therefore, the level of awareness of 3rd year students of the Faculty of Medicine about oral hygiene, ways to prevent The study of major dental diseases is of some interest. Goal of the work. Determination of the level of knowledge of 3rd year students of the Faculty of Medicine of the Samarkand State Medical University based on survey data on oral hygiene and prevention of major dental diseases diseases.